HUBUNGAN DUKUNGAN SOSIAL DENGAN PRESTASI BELAJAR MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2011 - Awalia, Mia Rizki; Hamidy, Muhammad Yulis; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Social support is one of the factors affect learning achievement. Socialsupport are attention, love, and advice that will give positive effect toward thestudents. The purpose of this study was to determine correlation of level study skillwith learning achievement of Medical Faculty students of Riau University batch2011. The study design was analytic with cross sectional method . The subject of thisstudy was Medical Faculty students of Riau University batch 2011. This study samplewas taken by total sampling technique. This study used a questionnaire of socialsupport and social support Study Results Card ( SRC ) to measure learningachievement . Statistical test used for correlation of social support with learninugachievment was Spearman test. The statistially study results showed there was nosignificant correlation between social support learning achievement. The conclusionof this study was most of students have categorie high social support and most ofstudent (Grade Point Avarage) GPA category were very satisfying.Keywords: social support, learning achievement